An introduction to Buddhist philosophy - "Laumakis, Stephen J" (New Delhi, 2016)
In this clearly written undergraduate textbook, Stephen Laumakis explains the origin and development of Buddhist ideas and concepts, focusing on the philosophical ideas and arguments presented and defended by selected thinkers and sutras from various traditions. He starts with a sketch of the Buddha and the Dharma and highlights the origins of Buddhism in India. He then considers specific details of the Dharma with special attention to Buddhist metaphysics and epistemology and examines the development of Buddhism in China, Japan and Tibet, concluding with the ideas of the Dalai Lama and Thich Nhat Hanh. In each chapter he includes explanations of key terms and teachings, excerpts from primary source materials and presentations of the arguments for each position. His book will be an invaluable guide for all who are interested in this rich and vibrant philosophy.
Keywords: Philosophy